Contact dynamic response with misalignment in a flexible rotor/magnetic bearing system - P. S. Keogh (2018)
This paper investigates the vibration characteristics of rotor displacement signals in a magnetic bearing system under conditions when rotor contact with auxiliary bearings is possible. Since these signals may be used for feedback control, it is necessary to determine how they may affect the ability of the controller to regain rotor levitation. An experimental system is used to demonstrate the sensitivity of the rotor nonlinear dynamic behavior to unbalance, which is sufficient to cause contact during rotor run-up through rigid-body and flexural mode critical speeds. Complex rotor dynamics may involve contact with more than one auxiliary bearing or bush. Application of appropriate rotating forces to the rotor through a magnetic bearing is also shown to induce similar contact dynamics. Thus, an alternative procedure for assessing the nonlinear rotor dynamic behavior is established with the potential for identification of appropriate control forces. The contact dynamics are also considered in the presence of auxiliary bearing misalignment. Misalignment may arise through physical translation of a housing or through steady-state offset errors in sensor measurements. A misalignment of 50% of the nominal radial clearance is applied at an auxiliary bearing. Various contact modes are evident as the rotor is run up in speed. During rundown, different contact dynamics may be encountered and the level of such hysteresis is assessed. Copyright © 2006 by ASME.